Construction of the Historical and Cultural Media Landscape in Regional Media - Elena V. Shashkova (Гуманитарный вектор)
The cultural space of the city is one of the most modern and relevant areas of research into the possibilities of identifying modern cities. Today, the media play a key role in the construction of the cultural media space, which largely determines both the “face” and “soul” of a modern city (both a metropolis and a provincial outback). When designing and implementing regional cultural policy, the central place is given to the unique cultural content of the place. This factor determines the relevance of the work. The object of the study is the media texts of the regional cultural and educational magazine “Omsk Muse”. The purpose of the study is to identify the problematic and thematic originality and historical context of media texts that implement the processes of construction and reproduction of the cultural media space of Omsk. Empirical material is media texts from the magazine “Omsk Muse”. The chronological period of the study is from 2008 to 2020. A total of 30 issues of the journal were analyzed. The following research methods were used in the work: general scientific methods of observing the material and describing it, the method of historicism, the method of content analysis, the method of discourse analysis, the cultural method, the method of functional analysis. In the course of the study, the content of the concept “cultural space of the city” was outlined, the specifics of the media space and media images as factors of modern cultural identification were considered; the functions of the media are highlighted, with the help of which the cultural “face” of the region is formed. Based on the study of empirical material using content analysis, the problematic and thematic features of publications devoted to the cultural and historical image of the city were identified. The research materials can be used in the development of lectures and practical classes in the disciplines “Regional Media”, “Art Journalism”, “Leisure Journalism”.